âICEâ â A rare cause for coagulopathy in a case of massive post-partum hemorrhage - Singh Gill, Navkiran; Jaan Perng, Cheow; Vong Liew, Alice (Bali Journal of Anesthesiology, 2017)
A case of massive post-partum hemorrhage in East-Malaysia, associated with 3-4 methylene-dioxy-methamphetamine (MDMA) abuse otherwise known as Ecstasy or locally as âICEâ, injected by the patient as a means to suppress labor pains prior to hospital presentation. We report a rare case of substance abuse that lead to life threatening hemorrhage in a maternal patient of productive age group. Presenting to the labor suite in second stage of labor in breech presentation, exhibiting active neuropsychiatric symptoms of intoxication like euphoria, drowsiness, mydriasis but able to obey commands. A rapid response by the Obstetric on-call team proceeded with an assisted-breech delivery. Post-delivery, a baby girl with poor Apgar score was born and intubated. The mother was then posted for an Examination Under Anesthesia as she was noted to have slow blood oozing per-vaginally using a single shot spinal as she exhibited features of difficult intubation and high risk of aspiration. During the procedure, she tipped into massive PPH complicated with DIVC, and was rushed into the intensive care unit for stabilization and back into the operation theatre, needing a total abdominal hysterectomy (TAH) as definitive bleeding control. She required large scale resuscitative efforts peri-operatively including continuous veno-venous hemofiltration (CVVH) as well as regional intensive care consultation. We describe, chronologically the anesthetic challenges faced in managing a patient in acute substance intoxication at presentation to our district hospital during twilight hours. We then explain the pharmacodynamics of MDMA in provoking coagulopathy. No reports of similar cases in the South-East Asia region.